Dynamic simulation and optimization of a urea granulation circuit - Cotabarren, Ivana María (2009)
A dynamic flowsheet for a complete urea granulation circuit is presented in this work. This flowsheet is based on previous validated models against industrial data for the crusher and screen and on a new model for the granulation unit. All three units are integrated under the gPROMS Molder Builder Environment, which allows having a powerful tool for the simulation and optimization steps. A sensitivity analysis is performed in order to evaluate the influence the different operating variables on the product and recycle streams. Finally, an optimization is carried out to determine the values of the manipulated variables that maximize the production under specification.